(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The article describes the current problems and perspectives of teaching informatics and ICT, as well as the professional form and educational environment, based on the analysis of experimental data, as well as the experience and reflection of the author’s pedagogical activity. Teacher development takes place in a modern school. The age-related characteristics of students’ thinking are considered, the results of a survey conducted among college students are presented, and the principle of convenience in teaching is described. In the educational process, examples of the use of Internet services were given in computer science classes